Penerapan Good University Governance terhadap Kepuasan Mahasiswa dengan Excellent Service sebagai Variabel Moderasi - Putrika, Kadek Eti; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 31 No 11 (2021)DO - 10.24843/EJA.2021.v31.i11.p02, 2021)
This study aims to determine the extent of the influence of the implementation of good university governance, excellent service in increasing student satisfaction at the Faculty of Economics and Business, Udayana University. Respondents were 100 people who were members of one of the student institutions within the Faculty of Economics and Business, Udayana University. The sampling method in this study used purposive sampling. The data analysis technique used is Moderated Regression Analysis (MRA). The results of the analysis show that there is a relationship between good university governance and student satisfaction. There is a relationship between excellent service and student satisfaction. Excellent service strengthens the influence of good university governance on student satisfaction. Keywords : Good University Governance; Excellent Service; Satisfaction.